PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (StudiPada Kantor AkuntanPublik Di Kota Semarang) - Yunita Nanda Sari, 14.05.52.0094; Kartika, Andi (Students' Journal of Accounting and Banking, 2018)
This study examines the factors that influence audit quality with one of the variables that moderates other variables in the Public Accounting Firm (KAP) in the city of Semarang by using the auditor's analysis unit working in the Public Accounting Firm (KAP). The sample research method uses a quantitative research method, that is, the type of research that is systematic, well-planned, and clearly structured from the beginning to the making of its research design using many numbers, ranging from data collection, interpretation of the data, and appearance of the results. The results showed that the competence and ethics variables of auditors had a positive and significant influence on audit quality. The independence variable does not affect audit quality. Ethical variables of auditors do not moderate the influence of competencies on audit quality. Ethical variables auditors moderate the effect of independence on audit quality. Keywords: Competence, Independence, Auditor Ethics and Audit Quality